Water column raw data (Kongsberg EM 122 entire dataset) of RV SONNE during cruise SO305 - Bange, Hermann W; Schumacher, Mia (PANGAEA, 2024)
Raw water column data were collected aboard RV SONNE during cruise SO305 using a 12kHz Kongsberg EM 122 multibeam echosounder. The expedition took place during 10.04.2024 - 22.05.2024 from Colombo (Sri Lanka) to Singapur in the Gulf of Bengal. The major aim of SO305 - BIOCAT-IIOE2 is to quantify key (micro)biological processes in the water column and ocean/atmosphere exchanges to assess their impact on the Oxygen Minimum Zone of the Bay of Bengal. Data were recorded outside EEZs. Sound velocity profiles (SVP) were applied on the data for calibration. Please see the cruise report for details. The data are unprocessed and can therefore contain incorrect depth measurements (artifacts) if not further processed. Note that refraction errors may occur when no proper SVP is applied. Data provision is part of the DAM Underway Project and published according to the FAIR principles.
Keywords: Bathymetry; Multibeam Echosounder